Pengambilan Rekaman dan Penyebaran Potongan Film Tanpa Hak - Victoria Bianca Uruilal; Rory Jeff Akyuwen; Agustina Balik (PATTIMURA Law Study Review, 2023)
ABSTRACT: Film is one type of cinematographic work, where cinematographic work itself is a creation protected by Law Number 28 of 2014 concerning Copyright in Article 40 paragraph (1) letter (m). However, in reality, there is an act of taking footage and distributing film cuts without rights carried out when someone watches a movie in a theater and uploads it on social media and gets economic benefits from the upload of the film cut. While clearly stated in the Copyright Act, which explains that creators and copyright holders have economic rights (Article 9) and moral rights (Article 5) to the creations they make, This right is only owned by creators and copyright holders; others are required to obtain permission. This research is normative juridical research conducted with a statutory approach, a conceptual approach, and primary, secondary, and tertiary legal sources. The act of taking footage and distributing film cuts without rights is part of commercial activities that benefit not the creators and copyright holders of copyright. If Article 43 letter (d) of Law Number 28 of 2014 concerning copyright is reversed, then it is an offense that violates Moral Rights in Article 5 and Economic Rights in Article 9. As for the violation being part of the tort, then the act of taking footage and dissemination of film cuts without rights has been contrary to the Civil Code in Article 1365, which is entitled to be held accountable on the basis of the element of fault, and the form of liability is compensation, both in the form of material and immaterial.